(untitled) (Encuentros, 2021)
Open source rhetoric is increasingly being applied to culture, but there is little consensus on what it means in this area. The objective of this work is to understand the translation processes of linguistic knowledge from the free and open source software movements to the circulation of cultural works during the 2000s. The qualitative research methodology used is the multiple case study. The units of analysis are the Open Access, Open Knowledge and Free Cultural Works initiatives. The technique used is the documentary review. The article explores the resignifications produced in the translations and points out a group of non-profit organizations governing these processes.